A comparison of muscle activation and knee mechanics during gait between patients with non-traumatic and post-traumatic knee osteoarthritis. Issue 7 (July 2019) - Robbins, S.M.; Morelli, M.; Martineau, P.A.; St-Onge, N.; Boily, M.; Dimentberg, R.; Antoniou, J.
Summary: Objective: The objective was to compare muscle activation and knee mechanics during gait between participants with non-traumatic knee osteoarthritis (OA), post-traumatic knee OA, and healthy adults. Design: Participants with non-traumatic knee OA ( n = 22), post-traumatic knee OA ( n = 19), and healthy adults ( n = 22) completed gait trials for this observational, cross-sectional study. Post-traumatic OA group had a history of traumatic anterior cruciate ligament (ACL) rupture. Surface electromyography (EMG) measured activation of seven lower extremity muscles. Motion capture cameras and force plates measured motion and force data. Principal component analysis (PCA) determined waveform characteristics (principal components) from EMG, knee angle, and knee external moment waveforms. Analysis of variance (ANOVA) examined group differences in principal component scores ( PC-scores ). Regression analyses examined if a variable that coded for OA group could predict PC-scores after accounting for disease severity, alignment, and lateral OA. Results: There was lower gastrocnemius EMG amplitudes ( P < 0.01; ANOVA) in the post-traumatic OA group compared to healthy group. Non-traumatic OA group had higher vastus lateralis, vastus medialis, and rectus femoris EMG compared to post-traumatic OA group ( P = 0.01 to 0.04) in regression analyses. Also, non-traumatic OA group had higher and prolonged lateral hamstring EMG compared to healthy ( P = 0.03; ANOVA) and post-traumatic OA ( P = 0.04; regression) groups respectively. The non-traumatic OA group had lower knee extension ( P < 0.05) and medial rotation ( P < 0.05) moments than post-traumatic and healthy groups. Conclusions: Muscle activation and knee mechanics differed between participants with non-traumatic and post-traumatic knee OA and healthy adults. These OA subtypes had differences in disease characteristics that may impact disease progression.